Post‐COVID Hypertension With Hyperreninemic Hyperaldosteronism in a Pediatric Patient - Vivian Shi; Teresa Trinka; Mohammed Faizan (Clinical Case Reports)
ABSTRACT COVID‐19 infection may predispose patients to long‐term renovascular complications. Early recognition and management are crucial for optimal outcomes. This case report underscores the importance of thorough follow‐up care for children recovering from COVID‐19, with a focus on monitoring blood pressure and renal function to mitigate long‐term renovascular disease.